The ockhamist heritage in modern political and legal philosophy (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
The present article tries to show and to demonstrate the influence of the late-medieval voluntarism –both in its escotic version and mainly in the ockhamist– in the modern political and juridical philosophy. Part exposing in synthetic form the fundamental principles of Ockham's philosophy to later analyze some of its consequences, among which the contingentism of  law and methodological individualism stand out.
Keywords: Ockham; legal contingentism; individualism; modernity